Agricultural biodiversity in the Tajik Pamirs - Giuliani, A.; Oudenhoven, F.J.W. van; Mubalieva, S. (International Mountain Society (IMS) and United Nations University, 2011)
This study investigates the role that local fruit varieties can play in achieving the dual objectives of food sovereignty and income generation in the Tajik Pamir Mountains. In this very harsh environment, agriculture is characterized by a great diversity of fruit varieties central to local food culture and household security. Local fruit trees can grow in poor soils on slopes and their resistance to diseases, cold, and ultraviolet light give them marked advantages over introduced varieties. However, the humanitarian crisis following the collapse of the Soviet Union and recent efforts by development organizations to create markets by introducing exotic varieties are negatively affecting agricultural biodiversity (agrobiodiversity) and, potentially, household security. A study was carried out in 3 districts of the Gorno-Badakhshan province to investigate the household consumption and market potential of products derived from local varieties of apple, apricot, and mulberry and how these products could be better exploited to benefit community livelihoods and agrobiodiversity conservation.